Pelatihan Tajhizul Mayyit Bersama Murid-Murid TPQ Al-Muhajirin di Jorong Pemukiman Baru II Kecamatan Koto Balingka Kabupaten Pasaman Barat - Muhammad Panogu; Ahmad Munawwir Nasution (Karsa : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to increase the knowledge and skills of TPQ Al-Muhajirin female students and female students in Jorong Semukiman Baru II, Koto Balingka District, West Pasaman Regency, regarding procedures for caring for corpses in Islam. This training was carried out using a Participatory Action Research (PAR) approach which included two main stages: conveying theory about laws and procedures for caring for corpses, as well as direct practice. Apart from that, theservice team develops learning applications and videos as tools to help in the educational process.  This training took place on August 20 2024 and was attended by 25 participants from the TPQ Al-Muhajirin Al-Qur'an class. Training resource person, Wahidatun Hidayah S.Pd. deliver material using interactive and practical methods. The results of this activity showed a significant increase in participants' understanding of the procedures for caring for corpses and the use of applications to support learning. This program is ef ective in enriching students' knowledge and facilitating a more ef icient and comprehensive learning process.